Social Network of Bugis Weavers at Wajo Regency, South Sulawesi - Muhammad, Syukur - (Komunitas, 2016)
The penetration of market economic system and the development of weaving technology within Wajo society has polarized Wajo weavers into three groups, Gedongan weaver, ATBM weaver and weaving entrepreneur. It indicates a different economic action conducted by those three groups in responding the economic market and technology development. This research aims to describe the moral basic in developing and utilizing network in weaving activities practiced by the three groups. The research uses qualitative approach with constructive paradigm. Data collection techniques used are in-depth interview method, participative observation and documentation. Data is analyzed using data reduction, presentation and conclusion. Research result indicates that production and distribution network of weavers involve social solidarity and economic interest and those networks take place in the form of horizontal and vertical relationship.Gedongan weavers use social solodarity network more than economic interest network. ATBM weavers tend to be in between solidarity and economic interest. Whereas, weaving entrepreneur use economic interest network more than solidarity network.